Mobile cauda equina schwannomas: How to deal with this rare event and avoid surgical complications - Onishi, Franz Jooji (Surg Neurol Int, 2018)
BACKGROUND: Mobile schwannomas of the cauda equina are rare. Preoperative planning should take into consideration the possibility of tumor migration, avoiding unnecessary additional laminectomy or second operation. CASE DESCRIPTION: A patient with a previously known lumbar schwannoma was being managed conservatively until symptoms exacerbated and led to a new MR. When this study revealed caudal migration of the schwannoma from L3 to the L4–L5 levels, a right hemilaminectomy was performed for tumor resection. CONCLUSION: Great care must be taken in the surgical resection of schwannomas as they may migrate from their initial location.